The genetic predisposition increases the chances of schoolchildren maintaining higher adiposity levels after three years - Éboni Marília Reuter; Cézane Priscila Reuter; João Francisco de Castro Silveira; Ana Paula Sehn; Pâmela Ferreira Todendi; Andréia Rosane de Moura Valim; Javier Brazo-Sayavera; Elza Daniel de Mello (BMC, 2023)
Abstract Background The behavior of anthropometrics and the relationship with genetic factors through a long-term perspective should be better explored. This study aims to verify the odds of maintaining the nutritional status classification after three years, according to the rs9939609 polymorphism (FTO gene). Methods It was a retrospective longitudinal study with 355 schoolchildren (7-17 years). Body mass index, body-fat percentage (BF%), and waist circumference (WC) were measured at baseline and follow-up. The FTO gene was evaluated from blood collection and genotyping performed by real-time polymerase chain reaction. Odds ratios and 95% confidence intervals were calculated. Results For those homozygous with the A allele, the odds of being at less favorable classification at follow-up were 2.29 (1.24; 4.22) and 4.05 (2.08; 7.86) times higher than expected for BF% and WC, respectively, whereas the odds of being in the more favorable classification at follow-up were 0.34 (0.12; 0.93) and 0.11 (0.01; 0.78) for BF% and WC, respectively. The odds of being at less favorable classification were higher for AA carriers with less favorable classification at baseline for BF% and WC compared to AT and TT carriers. Conclusions Schoolchildren with a genetic predisposition to obesity and unfavorable anthropometric profile at baseline had more chances of maintaining their nutritional status after three years of follow-up.